Modelo de planeación estratégica para pyme del sector construcción (2021)
This monograph seeks to develop a strategic planning model for a MSMEs in the construction sector in Colombia, based on the collection of information on the management and current administrative and operational situation of a particular company, G&B INGENIERIA SAS, a company dedicated to construction of multifamily housing with 13 years of experience in the National market, through this research work it is sought to have support for all small and medium construction companies that lack strategic planning in both Colombia and Latin America, for this analysis a bibliographic review of the different strategic approaches, adapting the one that best suits the organizational structure of the company, Fred David's strategic planning model.